Analisis Struktur dan Nilai Budaya Cerita Rakyat di Sekitar Waduk Jatigede Sumedang - Dian Sandiana; Retty Isnendes; Dingding Haerudin (Prodi Pendidikan Bahasa dan Sastra Daerah, 2024)
This research aims to inventory the folklore in the Sabudeureun Jatigede reservoir, Sumedang district. The aim is that all or part of the folklore can be documented, preserved and planned, in development efforts so that it can be utilized optimally to improve the quality of social life of the people in West Java. In addition, it is hoped that it can maintain, preserve and develop the cultural values contained therein which can be utilized optimally to improve the quality of people's social life. This research uses qualitative methods, namely understanding the phenomena experienced by the research subjects. Meanwhile, the research techniques used are library studies and field techniques. The data collection technique uses recording or noting informants' storytelling activities which are directed at being able to answer what and how the stories, local history or myths they have. Meanwhile, interviews are used to answer the meaning or cultural values contained therein. Apart from that, secondary data was also collected related to previous writings regarding descriptions of local history, myths and folklore related to the purpose of the writing. Meanwhile, the theories used in this research are structuralism and functionalism theories. The results of the research are folktales in the Jatigede reservoir, Sumedang Regency, which contain 40 folktales, namely: Endog Sapatalangan, Prabu Adji Putih, Prabu Tungtang Buana, Resi Patangjala Seda, Dewi Nawang Wulan, Dalem Santapura, Aji Putih Sungklanglarang, Babon Kadarmarajaan, Sasakala Weak Sagandu, Sasakala Sumedang Larang, Sasakala Darmaraja, Origins of Cipeueut, Origins of Cipaku, Sasakala Cieunteung, Sasakala Cimanuk, Sasakala Cau Manggala, Sasakala Halu jeung Lisung, Buhaya Putih jeung Keuyeup Bodas, Gunung Surian, Cadasngampar, Pasircalung, Jemah, Mount Jagat, Mount Lingga, Mount Simpay, Mount Cikalingsem, Mount Pamalayan, Mount Sangkan Jaya, Mount Bande, Mount Putri, Kampung Gorowong, Kampung Leuwi Hideung, Kampung Malember, Puncak Damar, Sasakala Paauthor, Sangkuriang version of Paauthor, Larasati Suwung Rasa, Asal -Suggestions for Overtime Pamelangan, Sasakala Kampung Karedok, and Sasakala Lebak Siuh. Furthermore, the content of the story does not focus solely on local history (historiography). Other stories appear as they occur in other areas, for example about sasakala (the origins of a place), cosmological stories, such as the world of spirits and ghosts and stories related to agriculture. Viewed in terms of function, this research aims to show identity which in turn builds the character of the community. Likewise, folklore can provide an understanding of the behavior of people who believe in supernatural beings